الحكم بن عبدل الأسدي بين الفكاهة والتهكم - عباس، سجا جاسم محمد Mohammed, Saja Jassem (جامعة بغداد - كلية الآداب, 2018)
Al –Hakam Bin Abdal Al-Isadi was a poet who appeared at the last of Umayyad Age. His style was characterized by collecting humor cynicism. The recent study , study 'Al- Isadi Between Humor and Cynicism 'sheds light on this poet,s character , and exposing his style of humor
Keywords: الأسدي، الحكم بن عبدل، ت. 106 هـ. -- التراجم -- العصر الأموي -- الشعراء الأمويين -- الدواوين والقصائد -- الفكاهة والتهكم -- نقد الشعر